Wildlife conservation and reduced emissions from deforestation in a case study of Nantu National Park, Sulawesi 1. The effectiveness of forest protection-many measures, one goal - Macdonald, E; Collins, M; Johnson, P; Clayton, L; Malhi, Y; Fisher, J; Milner-Gulland, E; Macdonald, D (2011)
Discussions on how to reduce carbon emissions from deforestation and degradation have prompted scrutiny of methods for measuring rates of forest loss, as well as discussion of the role of protected area (PA) status in reducing tropical deforestation. This study employs a range of techniques including GIS analyses and local stakeholder interviews to examine the effectiveness of three comparable PAs in Sulawesi, Indonesia in preventing deforestation over a 16-year period. Our analyses demonstrate that all three of the protected areas have proved effective at conferring forest protection to some extent, after controlling for other factors that influence deforestation rates. However Nantu Nature Reserve, the only recipient of broad-based conservation investment, proved to be substantially more effective than the PAs without international investment. In contrast with the recent hopes for integrating conservation with development, interviews with local stakeholders revealed that despite community development projects, the primary contributor to conservation had been the presence of a team of armed park guards. Despite the potentially divisive nature of this situation the villagers recognised the benefits of the forest and looked forward to a time when protectionism might be less necessary and instead villagers would be motivated primarily by the benefits rather than the costs of conservation. The use of remotely sensed data to evaluate conservation effectiveness in this data-poor region has challenges, but we demonstrate that, with the addition of contextualising data from locally based social surveys, it is possible both to quantify the additionality of individual PAs in preventing deforestation, after controlling for other factors, and to understand the reasons behind this success. This type of study will become increasingly necessary as REDD (reducing emissions from deforestation and degradation) implementation progresses. © 2011 Elsevier Ltd.